2012
DOI: 10.1074/jbc.m111.308916
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus NS5A Binds to the mRNA Cap-binding Eukaryotic Translation Initiation 4F (eIF4F) Complex and Up-regulates Host Translation Initiation Machinery through eIF4E-binding Protein 1 Inactivation

Abstract: Background: HCV infection results in hepatocellular carcinoma. mTORC1 and eIF4E regulate tumorigenesis through translation initiation. Results: HCV, through NS5A, activates mTORC1 and eIF4E, resulting in enhanced eIF4F assembly. NS5A binds to eIF4F complex and associates with polysomes. Conclusion: HCV up-regulates cap-dependent host protein translation machinery through NS5A. Significance: Activation of host translation machinery might facilitate HCV-associated hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 75 publications
0
40
1
Order By: Relevance
“…These effects may contribute to the establishment of persistent HCV infection, since PI3K and mTOR inhibition enhances HCV replication (37). Recently, NS5A protein has been shown to bind to the mRNA cap-binding eukaryotic translation initiation 4F (eIF4F) complex and to upregulate host translation (38). (iv) Protein folding.…”
Section: Main Biological Processes Regulated By Hcv At the Translatiomentioning
confidence: 99%
“…These effects may contribute to the establishment of persistent HCV infection, since PI3K and mTOR inhibition enhances HCV replication (37). Recently, NS5A protein has been shown to bind to the mRNA cap-binding eukaryotic translation initiation 4F (eIF4F) complex and to upregulate host translation (38). (iv) Protein folding.…”
Section: Main Biological Processes Regulated By Hcv At the Translatiomentioning
confidence: 99%
“…It has been shown by George et al 33 that HCV NS5A itself is able to activate mTORC1, which upregulates cap-dependent host protein translation and development of HCV-associated hepatocellular carcinoma. However, a direct link to viral replication and translation was not part of this study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, p38 MAPK activation and signaling is important for viral entry of reovirus and respiratory virus (Huang et al, 2011; Marchant et al, 2010). p38 MAPK signaling has also been implicated as playing a role in the viral transcription and translation of a number of viruses including hepatitis C virus, avian reovirus, porcine circovirus type 2, porcine reproductive and respiratory syndrome virus, rotavirus, Kaposi sarcoma-associated herpesvirus, encephalomyocarditis virus and HIV-1 (Cohen et al, 1997; George et al, 2012; Hirasawa et al, 2003; Jafri et al, 2007; Ji et al, 2009; Lee and Lee, 2012; Pan et al, 2006; Wei et al, 2009); and inhibition of p38 MAPK signaling has been shown to directly inhibit virus infection (Chang et al, 2008; Ludwig et al, 2003; Wei et al, 2009). EBOV infection induces MAPK signaling cascades in a GP-dependent manner, and p38 MAPK is thought to play dual roles in DC maturation and induction of inflammatory cytokines (Ayala et al, 2000; Lee et al, 2009; Terrazas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%